Tam protezlerde remounting işlemi - Nazlı Aktaş; Yasemin Özkan (Cumhuriyet University, 2013)
Occlusal discrepancies are one of the factors that cause the most discomfort among denture users. The existence of any discrepancies in the complete denture cause the patient have difficulties in the adaptation period. Remounting process is recommended when the denture is finished to correct occlusal conflicts. Remounting is a process in which the finished denture is adapted again on an articulator using individual records of the patient. In this review, the purpose and construction phases of remounting process is explained  respectively. Also the benefits provided by the remounting process such as reduced chairside time will be discussed in detail. Keywords: Remounting, complete denture. ÖZET Protez kullanıcıları arasında en çok rahatsızlığa sebep olan etken oklüzal uyumsuzluklardır.  Bunlar hastanın protezini kabul etmesi üzerinde çok etkililerdir. Bitmiş bir protezde herhangi bir erken temasın olmaması hastanın protezine adaptasyonunu çok kolaylaştırır. Hastaların protezlerinden memnuniyetini arttırmak için protezin tesliminden önce yapılan remounting; bitmiş protezin çeşitli kayıtlara dayanarak tekrar artikülatöre alınması işlemidir. Bu derlemede remounting işleminin neden gerekli olduğu ve yapım aşamalarından bahsedilecektir. Remounting işleminin klinik uygulamasındaki adımlar anlatılacak, bunun yanı sıra hastalara sağlayacağı avantajlarından bahsedilecektir.